Tele‐medicine and improvement of mental health problems in COVID‐19 pandemic: A systematic review. Issue 3 (14th June 2022) - Hatami, Hossein; Deravi, Niloofar; Danaei, Bardia; Zangiabadian, Moein; Shahidi Bonjar, Amir Hashem; kheradmand, Ali; Nasiri, Mohammad Javad
Abstract: Introduction: Tele‐medicine services have been developed in response to the COVID‐19 pandemic, which disrupts mental health services. The present study investigates the effectiveness of telephone‐delivered services for psychological disorders in the COVID‐19 pandemic. Methods: We searched PubMed/Medline, Embase and Cochrane Controlled Register of Trials for relevant clinical studies up to February 1, 2022. Following terms were used: "severe acute respiratory syndrome", "Coronavirus", "Coronavirus infection", "SARS‐CoV‐2", "COVID‐19", "mental disorder", "mental health", "mental health program", "mental health service", "psychiatric service", "telemedicine", "Telehealth", "Tele‐health", "Telecare", "Mobile health". Results: Twelve relevant clinical articles were included in our study. Eight articles were parallel randomized controlled trials (RCTs), two were Quasi‐experimental, and one was a multicenter retrospective cohort study. A total of 1900 adults (18 years old or above that) were included. Online telecommunication methods like online apps and videoconference were the most common interventions. The most prevalent measured outcome was levels of anxiety and depression among participants. Eleven out of 12 articles showed a significant association between telemedicine and mental health improvement. Conclusions: The included studies in the current systematic review reported the probable efficacy of telemedicine in improving mental health disorders during the COVID‐19 pandemic. But it is not possible to determine the best telecommunication method for each mental disorder in different populations and the preference of patients is still face to face therapy. So RCTs in different populations with previous mental disorders or chronic diseases are required to investigate the further telemedicine's efficacy on managing mental problems.